Structural Transformation : How Does Thailand Compare? - Klyuev, Vladimir (IMF Working Papers; Working Paper ;, 2015)
Thailand stands out in international comparison as a country with a high dispersion of productivity across sectors. It has especially low labor productivity in agriculture-a sector that employs a much larger share of the population than is typical for a country at Thailand's level of income. This suggests large potential productivity gains from labor reallocation across sectors, but that process-which made a significant contribution to Thailand's growth in the past-appears to have stalled lately. This paper establishes these facts and applies a simple model to discuss possible explanations. The reasons include a gap between the skills possessed by rural workers and those required in the modern sectors; the government's price support programs for several agricultural commodities, particularly rice; and the uniform minimum wage. At the same time, agriculture plays a useful social and economic role as the employer of last resort. The paper makes a number of policy recommendations aimed at facilitating structural transformation in the Thai economy.